Faust the theologian - Pelikan, Jaroslav, 1923-2006 (Yale University Press, 1995)
In this erudite and beautifully written book, an eminent scholar meditates on the theological implications of Goethe's Faust. Jaroslav Pelikan reflects on Goethe's statement that he was a pantheist when it came to science, a polytheist in art, and a monotheist in ethics, and he uses it for the first time to analyze Faust's development as a theologian. By so doing, Pelikan enables us to see Goethe's masterpiece in a surprising new light. Pelikan begins by discussing Faust's role as natural scientist or pantheist. He examines Faust's disenchantment with traditional knowledge, considers his interests in geology, oceanography, and optics, and analyzes his perception of nature as a realm inspirited throughout by a single unifying Power. Pelikan next follows Faust on his journeys to the two Walpurgis Nights, where he shows how Faust reveals his delight in the polytheistic extravaganzas of Germanic and especially of Greek mythology. Finally Pelikan describes the operatic finale of the book, where Faust's spirit is drawn upward to salvation by the Eternal Feminine, and he argues that this marks Faust's evolution into moral philosopher and monotheist. Pelikan's analysis thus reveals thematic unities and a dialectical development of Faust's character that have been unnoticed heretofore.